2022
DOI: 10.3390/vaccines10010113
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Mycobacterium bovis BCG Response to Macrophage Infection to Help Prioritize Targets for Anti-Tuberculosis Drug and Vaccine Discovery

Abstract: New strategies are required to reduce the worldwide burden of tuberculosis. Intracellular survival and replication of Mycobacterium tuberculosis after macrophage phagocytosis is a fundamental step in the complex host–pathogen interactions that lead to granuloma formation and disease. Greater understanding of how the bacterium survives and thrives in these environments will inform novel drug and vaccine discovery programs. Here, we use in-depth RNA sequencing of Mycobacterium bovis BCG from human THP-1 macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This suggests a clear orientation of Mtb lipid metabolism during early infection of MDMs toward modification of the lipid host-pathogen interface to modulate the host response and promote survival within the phagosome. In previously published analyses of the Mtb transcriptional response to the macrophage environment, the authors suggest rapid remodeling of metabolism to consume lipids, especially cholesterol, and activation of the metylcitrate cycle ameliorating lipid catabolism end-products (90)(91)(92)(93). However, our data show that the early stage of infection is not accompanied by any dramatic changes in central carbon and energy metabolism and shows no transcriptomic signs of lipid consumption/storage or nutrient starvation suggesting that macrophages are still abundant in diverse, readily available carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a clear orientation of Mtb lipid metabolism during early infection of MDMs toward modification of the lipid host-pathogen interface to modulate the host response and promote survival within the phagosome. In previously published analyses of the Mtb transcriptional response to the macrophage environment, the authors suggest rapid remodeling of metabolism to consume lipids, especially cholesterol, and activation of the metylcitrate cycle ameliorating lipid catabolism end-products (90)(91)(92)(93). However, our data show that the early stage of infection is not accompanied by any dramatic changes in central carbon and energy metabolism and shows no transcriptomic signs of lipid consumption/storage or nutrient starvation suggesting that macrophages are still abundant in diverse, readily available carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…In this progress, the activation of macrophages is of great importance. Medley et al ( 22 ) discovered potential vaccine and drug targets in the interaction of Mtb and macrophages, such as the enzymes encoded by Cytochrome P450 125 gene and Cytochrome P450 142 gene, which involved in the cholesterol metabolism of Mtb.…”
Section: Immune Response To Mtb Infectionmentioning
confidence: 99%
“…Ganzhu Feng et al developed a recombinant DNA vaccine based on nanoparticles, which contained three T cell epitopes of ESAT-6 and FMS-like tyrosine kinase 3 gene, and was encapsulated by chitosan (CS) nanoparticles. The results showed that the vaccine significantly enhanced T cell immunity and protected against Mtb H37Rv attack ( 22 , 164 ).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…Approximately one-third of the world’s population has a latent TB infection (LTBI), and about 10% can develop active tuberculosis (ATB) with impairment in the immune system ( Pai et al, 2016 ). In the host-pathogen interactions, intracellular survival and replication of Mtb after macrophage phagocytosis leads to an immune response that converges on granuloma formation and/or disease ( McCaffrey et al, 2022 ; Medley et al, 2022 ). The host cells have adopted a series of clearance mechanisms to facilitate intracellular bacterial killing, such as apoptosis, autophagy, inflammation, and macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%